Managing prolific sows in tropical environments - Tummaruk, Padet; De Rensis, Fabio; Kirkwood, Roy N. (Molecular reproduction and development, 2023)
Litter size in modern sows has been dramatically improved in recent decades by genetic selection for highly prolific sows. In a tropical environment, the average total number of pigs born and number born alive are reported to be as high as 17.2 and 15.1 piglets per litter, respectively. Therefore, the new production target in many herds aims to achieve 30–40 pigs weaned per sow per year. Despite the improvements in litter size, the mean preweaning piglet mortality rate remains high, at between 10% and 20%, in major pig‐producing countries. A sufficient daily feed intake by lactating sows is important for high milk production as sow milk yield is the limiting factor for piglet growth rate. Heat stress, which can occur when the ambient temperatures rise above 25°C, is one of the major problems that decreases daily feed intake and compromises milk yield. Therefore, it is necessary to encourage high feed intakes to achieve high milk yields. However, even with high nutrient intakes, productivity can be constrained by intestinal barrier function, limiting digestive ability, and allowing potential pathogens and/or toxins to become systemic. This is more likely greater under tropical conditions because of heat stress, exacerbating sow fertility problems. Underpinning sow herd performance, including responses to environmental challenges, is the selection of appropriate gilts, for example, selection and management for early puberty, thus presumably selecting the more fertile gilts and the correct management of lactation to improve the number of weaned piglets are some of the key factors for future reproductive efficiency of the farm under tropical conditions.